2019
DOI: 10.1155/2019/8393769
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell-Free Circulating MicroRNAs for the Detection of Early Breast Cancer and Molecular Subtyping

Abstract: Early detection is crucial for achieving a reduction in breast cancer mortality. Analysis of circulating cell-free microRNAs present in the serum of cancer patients has emerged as a promising new noninvasive biomarker for early detection of tumors and for predicting their molecular classifications. The rationale for this study was to identify subtype-specific molecular profiles of cell-free microRNAs for early detection of breast cancer in serum. Fifty-four early-stage breast cancers with 27 age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…In recent years, there is a great deal of studies demonstrated the genetic association between miRNAs and cancer, including lung cancer (Hu et al 2016) colorectal cancer (Schetter and Harris 2009) and breast cancer (Takahashi et al 2015, Kurozumi et al 2017. Several previous studies have demonstrated the value of plasma/serum miRNA in breast cancer diagnosis (Lagendijk et al 2018, Khodadadi-Jamayran et al 2018, Souza et al 2019. MiR-21 is involved in regulating the expression of multiple tumor suppressor genes, and plays a crucial role in the occurrence and development of a variety of diseases (Folini et al 2010, Peralta-Zaragoza et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is a great deal of studies demonstrated the genetic association between miRNAs and cancer, including lung cancer (Hu et al 2016) colorectal cancer (Schetter and Harris 2009) and breast cancer (Takahashi et al 2015, Kurozumi et al 2017. Several previous studies have demonstrated the value of plasma/serum miRNA in breast cancer diagnosis (Lagendijk et al 2018, Khodadadi-Jamayran et al 2018, Souza et al 2019. MiR-21 is involved in regulating the expression of multiple tumor suppressor genes, and plays a crucial role in the occurrence and development of a variety of diseases (Folini et al 2010, Peralta-Zaragoza et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report exhibited a differential expression of exosomal miR-101 and miR-373 in patients with breast cancer and benign breast tumors; exosomal miR-101 serum levels are deregulated in HER2-positive breast cancer in comparison to its levels in healthy women [113]. A recent study also analyzed ci-miRNAs in serum of breast cancer patients to identify subtype-specific molecular profiles of cell-free miRNAs for early detection of breast cancer in serum; the NanoString platform identified the 42 significant differentially expressed ci-mi-RNAs in each molecular subtype [114]. Of these 42, only four ci-miRNAs (ci-miRNAs-548ar-5p, 584-3p, 615-3p and 1283) are expressed in the HER2-positive subtype [114].…”
Section: Circulating Mirnas In Her2-positive Breast Cancermentioning
confidence: 99%
“…A recent study also analyzed ci-miRNAs in serum of breast cancer patients to identify subtype-specific molecular profiles of cell-free miRNAs for early detection of breast cancer in serum; the NanoString platform identified the 42 significant differentially expressed ci-mi-RNAs in each molecular subtype [114]. Of these 42, only four ci-miRNAs (ci-miRNAs-548ar-5p, 584-3p, 615-3p and 1283) are expressed in the HER2-positive subtype [114].…”
Section: Circulating Mirnas In Her2-positive Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations